(untitled) (American Journal of Energy and Natural Resources, 2022)
The rate of penetration (ROP) is one of the most important factors in improving drilling efficiency, is a measure of the speed or the progress of the drill bit when it drills subsurface formation. The study will be conducted with the input data sets of ROP, WOB, RPM, and all drilling data provided. To maximize the accuracy. In this paper, i collected data related to the rate of penetration from three wells in three different fields in Libya, and these fields are (Al-Sarir “the largest field in North Africa” - Amal field - Al-Sharara field). In the second stage, we will build an ROP model to compare the results of the rate of penetration in each well and each field. Finally, we make a recommendation on the best equation for each field, which gives results that are close to reality To be used to predict the rate of penetration in the future.